PERFORMANCE ASSESSMENT OF A SINGLE CHAMBER MICROBIAL FUEL CELL (MFC) (FUDMA JOURNAL OF SCIENCES, 2024)
Microbial fuel cells (MFCs) represent renewable energy technology with potential applications in electricity generation. This study aimed to construct and evaluate the performance of a single-chamber MFC using soil samples. Two MFCs were built for this purpose: one to assess performance by monitoring the variation of voltage and current over time, and the other to examine the effect of cathode surface area on MFC performance. Microbial fuel cells are important due to their potential to generate renewable energy, treat wastewater, remediate contaminated environments, serve as biosensors, and be scalable and integrated with other technologies, making them a promising solution for addressing various environmental and energy challenges. Notable results included recording maximum currents and voltages of 2.2 mA and 0.6 V, respectively, which elucidated the non-linear relationship between current and voltage. Additionally, it was found that the cathode surface area has a direct impact on the current produced. The polarization curve, illustrating current density as a function of voltage, was also analyzed. Another significant finding was a coulombic efficiency of 92.6%. Furthermore, connecting the MFCs in series achieved a voltage of 1.363 V. These results indicate substantial progress in the field. This study contributed to the advancement of MFC technology and its potential for practical applications in renewable energy generation, wastewater treatment, and environmental sustainability.
Keywords: Microbial fuel cells; Renewable energy; Environmental sustainability